How social face consciousness influences corrupt intention: Examining the effects of Honesty–Humility and moral disengagement. Issue 4 (4th July 2019) - Zhao, Huanhuan; Zhang, Heyun; Xu, Yan
ABSTRACT: This study aims to explore the relationship between social face consciousness and corrupt intention. Based on social cognitive theory, we established a mediated moderation model in which Honesty–Humility moderated the link between social face consciousness and corrupt intention, and moral disengagement mediated this moderating effect. Data were collected from an online survey of Chinese adults ( N = 1, 061) using self-administered questionnaires. Results revealed that Honesty–Humility cushioned the effect of social face consciousness on corrupt intention, such that this effect was stronger for individuals with low Honesty–Humility than for those with high Honesty–Humility. Findings also supported that the moderating effect of Honesty–Humility was partially mediated by moral disengagement. These results not only corroborate the critical role of social face consciousness in influencing corrupt intention but also shed some light on when and how social face consciousness results in corrupt intention. Implications and limitations were also discussed.